THE EFFECT OF AUDIT COMMITTEE CHARACTERISTICS AND WOMEN ON BOARD ON FIRM PERFORMANCE: AN ANALYSIS OF INDONESIAN MANUFACTURING FIRMS - Adeviani Fiardhani; Payamta Payamta (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Abstract The failures of several global companies caused by alleged financial statements fraud has created the awareness for the need of producing a quality of corporate financial reporting. Thus, the failures of several global companies reinforce the view that there is a critical need to improve the quality and reliability of the corporate financial systems through corporate governance in developed and emerging countries. This study aims to examine the characteristics of the audit committee and women on board on firm performance of manufacturing companies in Indonesia from 2019 – 2021. In order to investigate characteristics of the audit committee and women on board on firm performance of manufacturing companies in Indonesia, the dependent variable is firm performance (ROA, ROE, and Tobin’s Q). The independent variables in this research are audit committee characteristics (ACC), and women on board (WOMEN). Last, the moderating variables is family ownership (FAMILY). The result show that there is positive effect of ACC and WOMEN on firm performance. In addition, this result indicates that audit committee characteristic in family and non-family firm its different. This research is to provide further enrichment related to the problem of inconsistency in the relationship between audit committee characteristics and firm performance, especially there are not many such research in emerging countries such as Indonesia, especially regarding to the existence of strong family ownership in Indonesia companies. Keyword: Audit Committee Characteristics, Women on Board, Family Ownership, Firm Performance